Mountaineering in Malaysia: a review and discussion - Othman, Zainal Abidin; Yaakob, Sam Shor Nahar; Aziz, Azlizam; Ramlan, Mohd Aswad (Jabatan Perhutanan Semenanjung Malaysia, 2022)
Over the past 50 years, mountaineering activities have become increasingly popular in Malaysia. The significant rise in mountain forest climbing activities can be seen in the rapid growth of the emergence of associations and organisations, the presence of mountaineering enthusiasts, activists, and climbing practitioners on social media, and the formation of associations at higher education institutions. In line with current developments, government agencies also play an important role in directing the movement towards a balanced goal for forest conservation and the provision of quality mountaineering experiences among climbers. This paper provides an overview of climbing trends and challenges involving mountaineering activities and mountaineering scenarios in Malaysia. The importance of improved risk management, empowerment efforts, and strategic partnerships between authorities and industry actors to ensure the continuity of Malaysia's climbing activities is also emphasised.